CHITOSAN PRODUCTION FROM SQUID BONE Loligo. Sp WITH DIFFERENT CONCENTRATIONS OF SODIUM HYDROXIDE - Samsiana Arsyad; Krisman Umbu Henggu; Yatris Rambu Tega (Politeknik Kelautan dan Perikanan Dumai, 2023)
This study aims to examine the effect of different concentrations of NaOH (60%, 70%, and 80%) on the isolation process of chitosan from by-products of squid bone (Loligo sp). The resulting chitosan was then tested for water content, solubility, yield, degree of deacetylation, and functional groups. The results showed that the physical appearance of chitosan tends to be white, specific to the characteristics of commercial chitosan. The use of different NaOH concentrations only affects the water content. The water content of chitosan in the 70% and 80% NaOH treatments has met the maximum chitosan quality standard of 12%. The highest chitosan solubility was obtained in the 70% NaOH treatment, namely 97.76%. Likewise, the best degree of chitosan deacetylation reached 95% (70% NaOH treatment), while the average yield of chitosan obtained reached 25.55%. In general, the absorption values of functional groups in the NaOH treatment (60%, 70%, 80%) showed that there were characteristics of chitosan, namely carbonyl (C=O) and amino (N-H2) vibrations in the fingerprint area ( 1500–3000 cm-1). and a widening of the absorption band 1600-3500 cm-1 caused by O-H stretching and N-H vibrations due to deacetylation. Other characteristics are aliphatic C-H vibrations, –NH bond deformation, and glycosidic chitosan (C-O-C) vibrations at a wavelength of 664–1600 cm-1.